DCK negatively regulates the NRF2/ARE axis and ROS production in pancreatic cancer. (27th April 2018) - Hu, Qiangsheng; Qin, Yi; Xiang, Jinfeng; Liu, Wensheng; Xu, Wenyan; Sun, Qiqing; Ji, Shunrong; Liu, Jiang; Zhang, Zheng; Ni, Quanxing; Xu, Jin; Yu, Xianjun; et al.
Abstract: Objectives: Decreased deoxycytidine kinase (dCK) expression is a reported indicator of gemcitabine efficacy in pancreatic cancer, due to the impact of this kinase on gemcitabine metabolism. The transcription factor NF‐E2 p45‐related factor 2 (NRF2, also called Nfe2l2), a master regulator of redox homoeostasis, has been reported to tightly control the expression of numerous ROS‐detoxification genes and participates in drug resistance. However, the contribution of dCK to the NRF2 signalling axis has seldom been discussed and needs investigation. Materials and methods: By overexpressing dCK in pancreatic cancer cells, we assessed the impact of dCK on NRF2 transcriptional activity. Furthermore, we measured the impact of dCK expression on the intracellular redox balance and reactive oxygen species (ROS) production. By utilizing immunohistochemical staining and tissues from pancreatic cancer patients, we assessed the correlation between dCK and NRF2 expression. Through proliferation and metastasis assays, we examined the impact of dCK expression on cell proliferation and metastasis. Results: dCK negatively regulates NRF2 transcriptional activity, leading to the decreased expression of ARE‐driven antioxidant genes. In addition, dCK negatively regulates intracellular redox homoeostasis and ROS production. Negative correlations between dCK and NRF2 levels in pancreatic cancer cell lines and patient samples were observed. In vitro cell line studies suggested that dCK negatively regulated proliferation and metastasis. Conclusion: Decreased dCK expression promotes NRF2‐driven antioxidant transcription, which further enhances gemcitabine treatment resistance, forming a feedback loop.